Engineering Bilayer AlOx /YAlOx Dielectric Stacks for Hysteresis-Free Switching in Solution-Processed Metal-Oxide Thin-Film Transistors - Bolat, Sami; Agiannis, Evangelos; Yang, Shih-Chi; Futscher, Moritz H.; Aribia, Abdesselam; Shorubalko, Ivan; Romanyuk, Yaroslav E. (Frontiers in Electronics, 2022)
Solution processing and low-temperature annealing (T< 300°C) of the precursor compounds promise low-cost manufacturing for future applications of flexible oxide electronics. However, thermal budget reduction comes at the expense of increased charge trapping residuals in the dielectric layers, which result in hysteretic switching of transistors. This work reports on a novel bilayer dielectric scheme combining aluminum oxide (AlOx) as a positive charge trapping insulator and yttrium aluminum oxide (YAlOx) as a negative charge trapping dielectric to obtain hysteresis free switching in the solution-processed metal-oxide thin-film transistors. Devices were processed at a thermal budget of 250°C, without an encapsulation layer. The presence of H+ and OH- in the AlOx were found responsible for the hysteresis in the switching, which was suppressed successfully with the thickness optimization of the YAlOx in the dielectric stack. Fabricated devices yield ON/OFF ratios of 1e6, sub-pA level gate leakage currents, a subthreshold swing of 150 mV/decade, and field-effect mobility of 1.5 cm2/V-sec.